Multi-cracks modeling in reflective cracking - Pais, Jorge (2012)
Reflective cracking is a major concern for engineers facing the problem of road maintenance and rehabilitation. The problem appears due to the presence of cracks in the old pavement layers that propagate into the pavement overlay layer when traffic load passes over the cracks and due to the temperature variation. The stress concentration in the overlay just above the existing cracks is responsible for the appearance and crack propagation throughout the overlay. The analysis of the reflective cracking phenomenon is usually made by numerical modeling simulating the presence of cracks in the existing pavement and the stress concentration in the crack tip is assessed to predict either the cracking propagation rate or the expected fatigue life of the overlay. Numerical modeling to study reflective cracking is made by simulating one crack in the existing pavement and the loading is usually applied considering the shear mode of crack opening. Sometimes the simulation considers the mode I of crack opening, mainly when temperature effects are predominant. Thus, this paper presents a study where multiple cracks are modeled to assess the reflective cracking phenomenon and to compare to the case of only one crack. The modeling with only one crack was made simulating both mode I and mode II of crack opening taking into account the traffic effects. The influence of multiple cracks was expressed in terms of stress and strain in the zone above existing cracks. One of the conclusions from the current study is that the presence of multiple cracks can lead to a state of stress/strain higher than those obtained with only one crack. Also the position of the crack modeled in the finite elements analysis have a significant influence in the state of stress/strain obtained. However, the consideration of only one crack is sufficient to obtain significant results in the reflective cracking modeling.